Strain-encoded CMR for the detection of inducible ischemia during intermediate stress - Korosoglou, Grigorios; Lehrke, Stephanie; Wochele, Angela; Hoerig, Birgit; Loßnitzer, Dirk; Steen, Henning; Giannitsis, Evangelos; Osman, Nael F.; Katus, Hugo (JACC Cardiovascular imaging, 2010)
This study sought to evaluate the diagnostic accuracy of strain-encoded cardiac magnetic resonance (SENC) for the detection of inducible ischemia during intermediate stress. - Background - High-dose dobutamine stress cardiac magnetic resonance (DS-CMR) is a well-established modality for the noninvasive detection of coronary artery disease (CAD). However, the assessment of cine scans relies on the visual interpretation of wall motion, which is subjective, and modalities that can objectively and quantitatively assess the time course of myocardial strain response during stress are lacking.